Lateral stability of high-rise building - Gan, Ming Ong (2005)
Structural systems for tall buildings have undergone a dramatic evolution throughout the previous decade and into the 2000s. Developments in structural system form and organization have historically been realized as a response to as well as an momentum toward emerging architectural trends in high-rise building design. Traditionally, the primary concern of the structural engineer designing a building has been the provision of a structurally safe and adequate system to support the vertical loads. This is understandable since the vertical load-resisting capability of a building is its reason for existence. However, this is only true for the buildings involved if they were not too high, were not in seismic zones, or were constructed with adequate built-in safety margins in the form of substantial nonstructural masonry walls and partitions. For all the high-rise buildings, it is essential to take into account the lateral forces such as wind loads, seismic inertia-forces, blast loads, etc. to ensure the stability of buildings.